PABP and the poly(A) tail augment microRNA repression by facilitated miRISC binding - Moretti, Francesca; Hentze, Matthias W. (Nature structural & molecular biology, 2012)
Polyadenylated mRNAs are typically more strongly repressed by microRNAs (miRNAs) than their nonadenylated counterparts. Using a Drosophila melanogaster cell-free translation system, we found that this effect is mediated by the poly(A)-binding protein (PABP). miRNA repression was positively correlated with poly(A) tail length, but this stimulatory effect on repression was lost when translation was repressed by the tethered GW182 silencing domain rather than the miRNA-induced silencing complex (miRISC) itself. These findings are mechanistically explained by a notable function of PABP: it promotes association of miRISC with miRNA-regulated mRNAs. We also found that PABP association with mRNA rapidly diminished with miRISC recruitment and before detectable deadenylation. We integrated these data into a revised model for the function of PABP and the poly(A) tail in miRNA-mediated translational repression.